1997
DOI: 10.1104/pp.113.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a Protein Phosphatase from Chloroplast Stroma Capable of Dephosphorylating the Light-Harvesting Complex-II

Abstract: A protein phosphatase was purified from the stroma of Pea (Pisum sativum L.) chloroplasts that is capable of dephosphorylating synthetic phosphopeptides. Following chromatographic purification of greater than 400-fold, two-dimensional electrophoresis indicated that the stromal protein phosphatase is a 29-kD protein. A similar molecular size was determined for the protein-phosphatase activity using gel-permeation chromatography, indicating that the stromal protein phosphatase is probably a monomer. The purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
(35 reference statements)
0
22
1
Order By: Relevance
“…The presence of different phosphatases is one possible explanation for the various kinetic classes that were discerned in assays of endogenous phosphatase activity with isolated thylakoid membranes from pea (Pisum sativum) chloroplasts (Silverstein et al, 1993). The strong preference of PBCP for Mn 2+ and its insensitivity to NaF distinguish it from both the stromal and the membrane phosphatases active on LHCII phosphopeptides, which were previously purified from pea chloroplasts (Hammer et al, 1995(Hammer et al, , 1997. It is expected that further phosphatases involved in regulating thylakoid membrane structure and function remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of different phosphatases is one possible explanation for the various kinetic classes that were discerned in assays of endogenous phosphatase activity with isolated thylakoid membranes from pea (Pisum sativum) chloroplasts (Silverstein et al, 1993). The strong preference of PBCP for Mn 2+ and its insensitivity to NaF distinguish it from both the stromal and the membrane phosphatases active on LHCII phosphopeptides, which were previously purified from pea chloroplasts (Hammer et al, 1995(Hammer et al, , 1997. It is expected that further phosphatases involved in regulating thylakoid membrane structure and function remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Further work reported that another phosphatase activity, peripherally associated on the thylakoid membrane, can also dephosphorylate thylakoid proteins (Sun et al, 1989). Later on, a 29-kD stromal phosphatase was purified and found to be capable of dephosphorylating LHCII, too (Hammer et al, 1995(Hammer et al, , 1997. The activities of thylakoid protein phosphatases are independent of the redox states, and the kinetics of dephosphorylation reactions are heterogeneous among different substrates, including LHCII and PSII core subunits D1, D2, and CP43 (Silverstein et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Vener et al (10,11) have shown that the activation of the thylakoid protein phosphorylation involves binding of plastoquinol to the Q o site of the cytochrome b/f complex. Both thylakoid-bound (1,12,13) and soluble (14) protein phosphatases, active in dephosphorylation of thylakoid phosphoproteins, are reported to be present in plant chloroplasts.…”
mentioning
confidence: 99%